Equilibrium Existence in Incomplete Information Games with Atomic Posteriors - Nabil Al-Najjar; Eilon Solan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
We prove an existence result for games with incomplete information with continuous type spaces under the assumption that players have atomic posteriors. This information structure is an extreme example of the failure of absolute continuity of information, hence our result complements the classical result of Milgrom and Weber (1985).
Keywords: 330